Solar Cells: Corrugation Architecture Enabled Ultraflexible Wafer‐Scale High‐Efficiency Monocrystalline Silicon Solar Cell (Adv. Energy Mater. 12/2018). Issue 12 (26th April 2018) - Bahabry, Rabab R.; Kutbee, Arwa T.; Khan, Sherjeel M.; Sepulveda, Adrian C.; Wicaksono, Irmandy; Nour, Maha; Wehbe, Nimer; Almislem, Amani S.; Ghoneim, Mohamed T.; Torres Sevilla, Galo A.; Syed, Ahad; Shaikh, Sohail F.; et al.
Abstract : In article number 1702221, Muhammad M. Hussain and co‐workers demonstrate corrugation architecture enabled ultra‐flexible (140 mm bending radius), high performance (17.2% photovoltaic efficiency) crystalline silicon solar cells (each cell area 1276.2 mm 2 ) on a five‐inch wafer via a lithography‐less Complementary Metal Oxide Semiconductor (CMOS) compatible technique. The power conversion efficiency is comparable to the rigid Interdigitated Back Contact (IBC) module efficiency. The cells withstand 20% strain.